Motivational characteristics of recreational drug use among emerging adults in social settings: an integrative literature review - Lojszczyk, Alicja; Wilson, Rhonda; Wood, Jessica; Hutton, Alison (Frontiers in Public Health, 2023)
Introduction Recreational drug use by emerging adults has been identified as an increasingly normalized trend in social contexts. It has been documented that the consumption of these substances regularly occurs at music festivals, raves, nightlife and party settings. While it is known that emerging adults participate in these risk-taking behaviors, what is not known is their motivational characteristics for use. The aim of this review to identify and review literature describing the motivations for recreational drug use and drug choice (excluding alcohol, cannabis and tobacco) by emerging adults in social settings to inform selection of appropriately aligned harm reduction education and health messaging interventions. Methods Whittemore and Knafl’s (2005) integrative approach was used to conduct the review. This integrative review was based on a three-step search strategy identifying 2,772 articles published between 2000 and 2022. Eleven studies were included in the review. This review explores the following areas: drug use settings, concurrent drug use, consumer drug knowledge, motives of use including likes and dislikes and peer influence. Results A range of factors influence motivations of emerging adults to participate in recreational drug use. Similar to the consumption of alcohol, the use of recreational drugs by emerging adults is motivated by their perceived benefits and personal motivations to achieve euphoria, emotional intimacy, social benefits, peer influence, increased confidence and to decrease inhibitions. The review findings suggest that motivational factors that reinforce recreational drug use correlate with the desire to break away from the mundane by seeking pleasure and for the opportunity to create novel experiences. Beliefs about the positive and negative impacts of drug use, together with the desire to achieve emotional satisfaction influence drug taking activity. Conclusion Recreational drug use has become an increased societal norm amongst drug using peer groups and cannot be entirely prevented. It is to be noted that emerging adults have a basic understanding concerning recreational drugs, however, consumer drug knowledge and interventions that target illicit substances is lacking and should be addressed in future research. Festivals, raves and nightlife settings provide opportunity to implement health promotion as it reaches large number of vulnerable individuals in a short period of time.